2014
DOI: 10.2527/jas.2013-7222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, severity, and relationships of lung lesions, liver abnormalities, and rumen health scores measured at slaughter in beef cattle1

Abstract: An array of management tools exists within the beef industry to improve animal welfare and productivity; however, the ability to assess the outcomes of these tools is needed. Deficiencies in management commonly manifest as bovine respiratory disease complex or nutritional disorders such as acidosis; therefore, lung, liver, and rumen gross pathology lesions present at slaughter were measured as part of the Harvest Audit Program (HAP) and associations with performance determined. Individual gross pathology data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
7
38
0
4
Order By: Relevance
“…The lack of ruminal pathology in 2 of the steers with liver pathology suggests that liver abscesses may not exclusively be caused by ruminal lesions and is similar to that found previously (Rezac et al, 2014). The lack of ruminal pathology in 2 of the steers with liver pathology suggests that liver abscesses may not exclusively be caused by ruminal lesions and is similar to that found previously (Rezac et al, 2014).…”
Section: As Reported By the National Beef Quality Audit 2010 To 2011 supporting
confidence: 85%
See 1 more Smart Citation
“…The lack of ruminal pathology in 2 of the steers with liver pathology suggests that liver abscesses may not exclusively be caused by ruminal lesions and is similar to that found previously (Rezac et al, 2014). The lack of ruminal pathology in 2 of the steers with liver pathology suggests that liver abscesses may not exclusively be caused by ruminal lesions and is similar to that found previously (Rezac et al, 2014).…”
Section: As Reported By the National Beef Quality Audit 2010 To 2011 supporting
confidence: 85%
“…Moreover, Rezac et al (2014) reported a positive association between liver abscesses and ruminal lesions when assessed after slaughter. While the causative factors for liver abscesses and association between ruminal and liver lesions have been assessed, few studies have characterized ruminal fermentation in relation to formation of rumenitis and liver abscesses.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial observations linking AV lung lesions at packing plants to cattle that had never been observed to exhibit signs of BRD, there has been a continual flow of work published that documented similar findings (Thompson et al , 2006; Schneider et al , 2009; Leach et al , 2013; Busby, 2014; Rezac et al , 2014). The impact of BRD on growth has been variable but the range published by these researchers has been a decrease in ADG between 0.10 lbs day −1 and over 1 lbs day −1 .…”
mentioning
confidence: 93%
“…No entanto, a prevalência na maioria dos confinamentos varia de 12 a 32% (Nagaraja & Lechtenberg, 2007). Entretanto, dados recentes sugerem que a média se encontra entre 10 e 20% (Rezac et al, 2014). Com relação a incidência de abscessos hepáticos em bovinos confinados no Brasil, alguns trabalhos relatam a incidência de 2,5% e outros de 3,1% (Almeida et al, 2005, Vechiato et al, 2011.…”
Section: Incidênciaunclassified
“…Mas, em um estudo realizado por Rezac et al (2014) sobre a relação entre saúde ruminal e os abscessos hepáticos, verificou-se que 32% dos bovinos com ruminite moderada ou grave apresentaram abscessos hepáticos, já aqueles com a parede ruminal saudável a incidência foi de 19%.…”
Section: Patogêneseunclassified